Online Learning in Higher Education in Sub-Saharan Africa: Ghanaian University students' experiences and perceptions - Asunka, Stephen (International Review of Research in Open and Distributed Learning, 2008)
This study adopted a qualitative case-study approach to examine the attitudes, experiences, and perceptions of undergraduate students who were enrolled in an online, collaborative learning course at a Ghanaian private university. Data sources included surveys, student and instructor journal entries, email records, individual interviews, and Web-server logs. The study found that the students did not respond favorably to online constructivist teaching approaches such as asynchronous discussions and ill-structured project-based learning activities, and perceived collaborative online learning within their context as a complex, more demanding and time-consuming experience.